Citrate Promotes Nitric Oxide Production during Human Sperm Capacitation - Diego Loggia; Cristian O'Flaherty (MDPI AG, 2024)
Sperm capacitation is a complex process essential for the spermatozoon to recognize and fertilize the oocyte. For capacitation to occur, human spermatozoa require low levels of reactive oxygen species (ROS), increased protein tyrosine phosphorylation, and sufficient levels of energy metabolites such as citrate. Human spermatozoa are exposed to high concentrations of citrate from the seminal plasma, yet the role of citrate in sperm capacitation is largely unknown. We report that citrate can support capacitation in human spermatozoa incubated with no other energy metabolites in the capacitation medium. Reduced capacitation levels were observed in spermatozoa incubated with inhibitors of mitochondrial citrate transporter (CIC), cytosolic ATP-citrate lyase (ACLY), malic enzyme (ME), and nitric oxide synthase (NOS). The role of citrate metabolism in ROS production was further elucidated as citrate increased NO● production in capacitated spermatozoa, whereas inhibition of ACLY reduced NO● production. This research characterizes a novel metabolic pathway for citrate to produce NO● in the process of human sperm capacitation.